Beyond Deadlines: Academic Stress, Mental Health Risks, and Coping Inequities at Khulna University - Md. Fajlay Rabbi; Ummay Huraira Pranto; Md. Limon Sheikh (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Academic stress may be the single most dominant stress factor that affects the mental well-being of tertiary level students. The increasing prevalence of mental health issues among university students has become a global concern, particularly in the post-pandemic era. This study examined the prevalence of academic stress, its relationship with mental health symptoms, and coping strategies employed by students at Khulna University, Bangladesh. A cross-sectional survey was conducted among 366 university students across various schools and academic years. Data were collected using validated Likert-scale questionnaires measuring academic stress, mental health symptoms (depression, anxiety, and stress), and coping strategies. Statistical analyses included ANOVA and multiple regression models. Academic stress was highly prevalent, with 82.0% of students reporting excessive academic pressure from assignments. Mental health symptoms were common: 34.7% experienced depression, 28.7% reported anxiety, and 48.1% experienced stress over trivial matters. Social support (59.8%) was the most utilized coping strategy. Fourth-year students showed significantly higher stress levels (F = 17.52, p < 0.001). Extended academic stress positively impacts students' depression levels with a β of 0.293, consistent with our findings showing excessive academic pressure and unrealistic teacher expectations as significant predictors of both depression (β = 0.3172, p < 0.001) and anxiety (β = 0.4031, p < 0.001). Academic stress significantly impacts mental health among university students. Universities should implement comprehensive mental health support programs, establish realistic academic expectations, and promote effective coping strategies to address this growing concern.